Integrating peer feedback and instructor feedback to support the construction of bilingual scientific argument maps. Issue 15 (13th October 2022) - Archila, Pablo Antonio; Barbosa, Valentina; Gravier, Gissel; Levy, Laura; Ortiz, Brigithe Tatiana; Wilches, Luciana; de Mejía, Anne-Marie Truscott; Restrepo, Silvia
ABSTRACT: Recent studies show that the exploration of ways to involve students in effective bi/multilingual science education is gaining attention at all educational levels. Introducing students to the construction of bilingual scientific argument maps – visual representations of scientific argument structure using two languages – contributes to the quality of bilingual science education as they are a key aspect of bilingual scientific literacy; however, very little is known about how to promote the construction of these maps in bilingual science courses. Here we provide evidence for the claim that peer feedback and instructor feedback can be integrated to support the construction of bilingual scientific argument maps. A pedagogical strategy that integrates both peer feedback and instructor feedback was implemented in a university bilingual science course with 29 students (23 females and 6 males, 18–24 years-old) in Colombia. Results show that the strategy effectively supported the construction of scientific argument maps in Spanish and English. Implications for research and practice are discussed.